2015
DOI: 10.1155/2015/813242
|View full text |Cite
|
Sign up to set email alerts
|

Does Posterior Capsule Opacification Affect the Results of Diagnostic Technologies to Evaluate the Retina and the Optic Disc?

Abstract: The visual outcome obtained after cataract removal may progressively decline because of posterior capsular opacification (PCO). This condition can be treated by creating an opening in the posterior lens capsule by Nd:YAG laser capsulotomy. PCO optical imperfections cause several light reflection, refraction, and diffraction phenomena, which may interfere with the functional and structural tests performed in different ocular locations for the diagnosis and follow-up of ocular disease, like macular and optic ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…AKK, hastanın görüşünü azalttığı gibi muayene sırasında retina ve optik diskin izlenmesini ve gerektiği durumlarda çeşitli cihazlar ile görüntülenmesini de engelleyebilmektedir. [5][6][7][8] Günümüzde AKK tedavisinde neodymium: yttrium-aluminum-garnet (Nd:YAG) lazer en sık kullanılan tedavi yöntemlerinden biridir. 9 Nd:YAG lazer, cerrahi kapsülotomiye göre daha az invaziv olduğundan sıklıkla tecih edilen alternatif bir yöntemdir.…”
Section: Yoğun Arka Kapsül Kesafeti Olan Hastalardaunclassified
“…AKK, hastanın görüşünü azalttığı gibi muayene sırasında retina ve optik diskin izlenmesini ve gerektiği durumlarda çeşitli cihazlar ile görüntülenmesini de engelleyebilmektedir. [5][6][7][8] Günümüzde AKK tedavisinde neodymium: yttrium-aluminum-garnet (Nd:YAG) lazer en sık kullanılan tedavi yöntemlerinden biridir. 9 Nd:YAG lazer, cerrahi kapsülotomiye göre daha az invaziv olduğundan sıklıkla tecih edilen alternatif bir yöntemdir.…”
Section: Yoğun Arka Kapsül Kesafeti Olan Hastalardaunclassified
“…Posterior capsular opacification (PCO), also known as a secondary cataract, is a common long-term complication in which the eye lens lose transparency after lens implantation surgery in cataract patients [19,20]. As the most prevalent blindness disease in the world, currently the best way to treat cataract is by means of surgery to implant intraocular lenses (IOLs) [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, certain studies have shown no effect on the signal strength and image quality of scanned images with Spectral domain Optical Coherence tomography (SD-OCT). [ 4 5 ] OCT scans yield reliable thickness measurement of the macular before ND:YAG capsulotomy for PCO. [ 6 ]…”
mentioning
confidence: 99%